THE CONCEPT, GOAL, AND SOLUTIONS OF BUSINESS DIGITAL TOKENISATION IN DEVELOPING COUNTRIES, ON THE EXAMPLES OF ARMENIA - Karyan, Ara; Karyan, Vladimir (Bulletin of Yerevan University G: Economics, 2025)
The idea of a business model based on tokenized assets is used in the article to describe and build the concept and main approaches, criteria, tools of business digitalization. For competitiveness, high-quality, and inclusive growth of the real sector of the economy, the Republic of Armenia must focus on the paradigm of the digital economy with a matrix of information technology plus an exact industry of the real sector (IT + seprate  industries sectors). The benefits and advantages of the token-based business model toolset are outlined in detail in aspects of decentralisation, innovative responsiveness, immutability of entered information, cryptographic security, transparency, the ability to carry out peer-to-peer transactions without the need for verification and regulation by a central authority, and ultimately increasing the level of governance and efficiency, liquidity, and attraction of alternative investment vehicles. The systems of business decentralisation at the organisational and managerial level, various channels for the exchange and sale of tokens are interpreted.A concept has been put forward to solve the problems of digitalization in Armenia simultaneously: a) in the ICT sector, b) in the real sector of the economy, c) in the financial sector; and, of course, in the educational field. The concept of goal setting is built on the axis of convergent development, which, in turn, will bring a synergy result — a new quality of competitiveness for the beneficiaries of all the mentioned sectors as well as for consumers.It is emphasised that, in-depth understanding of the of the legal regulation of business digitalization is more important for the real sector of the economy, since it is aimed at ensuring: promotion of the generation of innovations; business management efficiency; reducing product and service costs and increasing productivity and efficiency of management; and disclosure of alternative investment channels for businesses.
Keywords: blockchain; distributed ledger technology (DLT); token; classification of token; tokenomics; digitalizition on convergence development